Governance of Village-Owned Enterprises for Food Security in West Bandung Regency - Dudi Supriadi; Yudi Rusfiana; Ali Hanafiah Muhi (Sean Institute, 2026)
This study aims to analyze the governance of Village-Owned Enterprises (BUMDes) in strengthening food security in West Bandung Regency, identify the supporting and inhibiting factors, and formulate strategies for optimizing BUMDes governance. The study employed a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving various stakeholders engaged in BUMDes management. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing in an interactive manner.The findings reveal that BUMDes governance in West Bandung Regency is supported by a relatively strong regulatory framework, including Government Regulation Number 11 of 2021, West Bandung Regency Regional Regulation Number 1 of 2024, and village regulations governing BUMDes operations. However, the implementation of governance has not yet been fully optimized due to limitations in human resource capacity, weak financial management, low digital literacy, limited market access, high feed costs, and the potential influence of political intervention in BUMDes management. The main supporting factors include regulatory support, village capital participation, local resource potential, and the commitment of local government institutions. BUMDes have contributed to job creation, increased village economic activities, and the stabilization of local food prices, although their impact on Village Original Revenue (PADes) and food security remains uneven.The study concludes that the optimization of BUMDes governance requires strengthening human resource capacity, digitalizing management and financial reporting systems, developing strategic partnerships, enhancing supervision and accountability mechanisms, and establishing business models integrated with food security programs. Consistent implementation of good governance principles will improve the effectiveness of BUMDes in supporting food security and enhancing the welfare of rural communities in West Bandung Regency.